Adjustment challenges and coping strategies of Arab female international university students - Nazir, Thseen; Özçiçek, Ayşe (Frontiers in Psychology, 2023)
With the increasing inflow of International students in Türkiye, the number of female Arab students also increased. So did the interest in understanding their adjustment challenges. This paper examines the adjustment challenges experienced by female Arab international students studying at universities in Türkiye. A mixed-method approach with International Students’ adjustment Scale (ISAS) and semi-structured interviews were utilized to understand the experiences of Arab female international students in these educational settings. The quantitative results revealed that Arab females are going through similar challenges in each dimension of adjustment, regardless of their country of origin. The qualitative results gave an in-depth understanding of these adjustment challenges and found that female Arab international students face various problems specific to gender, and related to the differences between Arab and Turkish cultures. Concerning their cultural background, participants reported that gender-related issues and practices in their home countries caused their adjustment process in Türkiye challenging. To deal with the adjustment challenges, they usually adopted maladaptive and dysfunctional coping strategies such as avoidance, isolation, and reluctance to ask for help.